2013
DOI: 10.1371/journal.pone.0068427
|View full text |Cite|
|
Sign up to set email alerts
|

Variation in Apical Hook Length Reflects the Intensity of Sperm Competition in Murine Rodents

Abstract: BackgroundPost-copulatory sexual selection has been shown to shape morphology of male gametes. Both directional and stabilizing selection on sperm phenotype have been documented in vertebrates in response to sexual promiscuity.MethodologyHere we investigated the degree of variance in apical hook length and tail length in six taxa of murine rodents.ConclusionsTail sperm length and apical hook length were positively associated with relative testis mass, our proxy for levels of sperm competition, thus indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
(80 reference statements)
1
19
1
Order By: Relevance
“…On the other hand, a recent attempt to relate sperm competition (analyzed by relative testes mass), sperm quantity, and traits that determine ejaculate quality among 18 rodent species revealed that sperm competition favors an increase in both sperm numbers as well as the proportion of normal, motile and acrosome-intact sperm (G omez et al, 2011). Varea-S anchez et al (2014) and Sandera et al (2013) later proposed that sperm competition favors the production of more uniform sperm heads and flagella, which lead to enhanced swimming velocityÀ Àparticularly in Apodemus proteases are inhibited by their endogenous antagonists (e.g., serpins), allowing the adhesive material between the sperm heads to maintain their association in a typical rosette morphology. B: Dilution of the epididymal caudal fluid in the female genital fluid or in chemically defined media leads to rosette disassembly.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent attempt to relate sperm competition (analyzed by relative testes mass), sperm quantity, and traits that determine ejaculate quality among 18 rodent species revealed that sperm competition favors an increase in both sperm numbers as well as the proportion of normal, motile and acrosome-intact sperm (G omez et al, 2011). Varea-S anchez et al (2014) and Sandera et al (2013) later proposed that sperm competition favors the production of more uniform sperm heads and flagella, which lead to enhanced swimming velocityÀ Àparticularly in Apodemus proteases are inhibited by their endogenous antagonists (e.g., serpins), allowing the adhesive material between the sperm heads to maintain their association in a typical rosette morphology. B: Dilution of the epididymal caudal fluid in the female genital fluid or in chemically defined media leads to rosette disassembly.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that has by far attracted most attention is that the apical hook evolved in the sperm of muroid rodents as an adaptation to sperm competition. This has been suggested after comparative studies found that the curvature (Immler et al ., ; Sandera et al ., ), shape (Immler et al ., ) and length (Sandera et al ., , ) of the sperm apical hook are positively correlated with inferred sperm competition measures in murine species. Interestingly, several species in different lineages of muroid rodents do not have an apical hook.…”
Section: Introductionmentioning
confidence: 92%
“…A further study (Fisher et al, 2014) revealed that although sperm aggregations tended to have higher progressive swimming velocities than single cells in the two species, P. maniculatus sperm aggregates in numbers that optimize the increase in velocity more frequently than P. polionotus. Based on this evidence, the notions that the sperm apical hook has evolved among muroid rodents as a facilitator or stabilizer of the formation of sperm aggregations and that sperm cooperation would represent an important adaptation to sperm competition, have received considerable attention (Moore et al, 2002;Immler et al, 2007;Pizzari & Foster, 2008;Fisher & Hoekstra, 2010;Foster & Pizzari, 2010;Sandera et al, 2011Sandera et al, , 2013Fisher et al, 2014). Furthermore, it has been argued that the apical hook could be a prerequisite for sperm associations (Higginson & Pitnick, 2011) and that the absence of a hook in some species could be a consequence of relaxation of sexual selection under conditions of low sperm competition (Roldan et al, 1992;Breed, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This process, however, may not be so straightforward, since genetic variation in traits under selection may be maintained through a number of mechanisms including, for example, trade-offs with other traits (Cattelan, di Nisio, & Pilastro, 2018;Immler et al, 2011) and mutation-selection balance (Zhang & Hill, 2005). Nevertheless, despite these mechanisms that may maintain genetic variation despite selection, empirical studies have often found that in species with intense post-copulatory sexual selection, spermatozoa were less variable in size, both between (Calhim, Immler, & Birkhead, 2007;Fitzpatrick & Baer, 2011;Kleven, Laskemoen, Fossøy, Robertson, & Lifjeld, 2008;Lifjeld et al, 2010) and within males (Fitzpatrick & Baer, 2011;Lifjeld et al, 2010;Šandera, Albrecht, & Stopka, 2013;Varea-Sánchez, Gómez Montoto, Tourmente, & Roldan, 2014), in comparison to species with a lower intensity of sexual selection. This observation is usually interpreted as evidence for strong stabilizing selection having depleted genetic variance in sperm length to favour the same optimal phenotype and consequently genotype in species with a high risk and/or intensity of sperm competition (Fitzpatrick & Baer, 2011;Lifjeld et al, 2010;Šandera et al, 2013;Varea-Sánchez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%